Tingkat Redam Suara Dan Ketahanan Papan Partikel Campuran Serbuk Kayu Sengon Dan Mesocarp Kelapa Sawit Terhadap Serangan Rayap Tanah: KUALITAS REDAM SUARA PAPAN PARTIKEL MESOCARP KELAPA SAWIT - Indrayani, Yuliati; Ferdiansyah, Adli; Setyawati, Dina; M., Iskandar A. (BRIN Publishing, 2025)
The increase in palm oil production in Indonesia produces significant volumes of waste, including empty fruit bunches (EFB), shells, and fibers. This waste has the potential to be processed into particleboard, with the addition of sawdust to improve physical properties and termite resistance. An additional raw material is Sengon wood (Falcataria moluccana (Miq.)), which was chosen due to its economic value and fast-growing nature. The purpose of this study was to determine its physical properties, resistance to subterranean termite attacks, and sound attenuation level. Particleboard was made from a mixture of oil palm mesocarp fiber and Sengon wood particles using urea formaldehyde (UF) adhesive with a concentration of 18%. The raw material combinations of oil palm mesocarp fiber and Sengon wood particles were 0:100, 25:75, 50:50, 75:25, and 100:0. Hot pressing was carried out at a pressure of 25 kg/cm² and a temperature of 130 °C for 10 minutes. The results of the study showed that the physical properties of the material ranged from 0.37 to 0.39 g/cm, water content from 7.27% to 9.45%, thickness expansion from 5.94% to 11.71%, and water absorption from 96.53% to 149.79%. The resistance of the board to subterranean termite attacks, achieved with a combination of oil palm mesocarp and sengon powder 75:25%, resulted in the highest termite mortality. In comparison, the combination of oil palm mesocarp and sengon wood powder (100:0%) experienced the highest weight loss. The best sound attenuation level was achieved with a combination of oil palm mesocarp and sengon wood powder 0:100%.